Methods of Teaching a Foreign Language in Technical Universities (Eurasian Research Bulletin, 2022)
This article provides examples from practice the author's work in teaching a foreign language in the classroom, justifies the effectiveness use of various methods in the process learning a foreign language at a technical university, the article is devoted to the effective use various methods and means in teaching foreign language